THE SAFE CEILING OF LITHUANIAN BUDGET DEFICIT - Kregždė, Arvydas (Ekonomika, 2013)
Abstract. The paper deals with the impact of the budget deficit on the outstanding debt of Lithuania. The ceiling of 3%, which is set in the Maastricht Treaty, is used as a benchmark to simulate changes of the outstanding debt. In addition, the influence of the interest paid on the debt to the primary budget deficit is analysed. The analysis shows that the rule of the Maastricht Ttreaty concerning the ceiling of 3% for a budget deficit is not sufficient to have a steady or non-increasing state of the debt of Lithuania. Great varieties of GDP growth and the initial outstanding stock of the debt in the EU countries allow a very substantial growth of the debt as well as a decrease of the debt for an individual country, despite the limit of 3% being in place. In order to a have non-increasing debt of Lithuania, the ceiling of the budget deficit should be flexible and lower than that set by the Maastricht Treaty. The conclusion is based on statistical data of the EU countries and the model of integral presentation form of the debt applied in the Lithuanian case.Key words: budget, deficit, debt, sustainability